A new configuration of composite nonlinear feedback control for nonlinear systems with input saturation. (March 2023) - Zhu, Quanmin; Mobayen, Saleh; Nemati, Hamidreza; Zhang, Jianhua; Wei, Wei
This study proposes a U-control–based Composite Nonlinear Feedback (U-CNF) design procedure. This U-CNF control establishes a double feedback loop framework for generalisation and simplification in designing the CNF control systems. Two controllers, in terms of double dynamic inversion, are designed separately, (1) to stabilise and cancel the nonlinearities and dynamics (convert the plant into an identity matrix) in the inner closed-loop, and then (2) to improve the system transient response by specifying a second-order linear system with a monotonic nonlinear function to smoothly tune the damping ratio. Accordingly, the conventional CNF characteristics in a concise pathway are achieved. The properties show, under proper conditions, the U-CNF control is plant model-free control, applicable to nonaffine nonlinear dynamic systems, and robust against model uncertainty and external disturbance. For the initial bench tests of the first-time proposed U-CNF configuration, the simulated case studies are provided with a transparent procedure to demonstrate the consistency with the analytical results in the numerical computations and to present guidance for applications.